Pro dan Kontra Peraturan Pemerintah No. 26 Tahun 2023 tentang Pengelolaan Hasil Sedimentasi di Laut: Perspektif Fiqh Siyasah Syar’iyyah - Reza Aditya; Tetty Marlina Tarigan (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Based on Government Regulation No. 26 of 2023 concerning management of sedimentation results in the sea, this research aims to find out the pros and cons that occur as a result of the ratification of Government regulation No. 26 of 2023 concerning management of sedimentation results in the sea and what is the perspective of siyasah syar'iyyah fiqh on Government regulation No. 26 of 2023 concerning management of sedimentation results in the sea. This research uses a descriptive type of normative juridical legal research to describe the pros and cons of PP No. 26 of 2023 concerning management of sedimentation results in the sea. The data sources are primary data and secondary data, the data collection technique uses qualitative library research in the form of books, scientific journals, language dictionaries and various other literature. The results of the research show that the opening of sea sand exports was opposed by a number of academics, environmental activists, non-governmental organizations and the DPR RI. The academic text that is the basis for drafting this regulation is considered premature, because it is not supported by the results of a comprehensive study regarding the potential distribution, locations of marine sedimentation that can be taken, sedimentation content, safe retrieval technology, and economic risks and prospects. Perspective of Siyasah Syar'iyyah Fiqh on Government Regulation No. 26 of 2023 concerning the management of sedimentation results in the sea is considered not in accordance with established Islamic law. This can be seen from changes in the system that reintroduced sea sand exports after 20 years of non-operation.